A "syncretism of piety": imagining global protestantism in early eighteenth-century Boston, Tranquebar, and Halle - Stievermann, Jan (Church history, 2020)
This essay reexamines the network centered on the Boston Congregational minister and theologian Cotton Mather, the great Pietist theologian August Hermann Francke, several of the latter's associates in Halle and London, and Halle-sponsored Lutheran missionaries in the Danish colony of Tranquebar. It pursues the question what this network (which existed from circa 1710 into the 1730s) reveals about how the idea of a "Protestant religion" evolved as a theological construct and how "Protestantism" as a category of religious identity came to have meaning and resonance across denominational and linguistic divides. Through the Boston-Halle-Tranquebar exchange, the essay argues, "awakened souls" from Anglo-American Reformed and German Lutheran churches converged toward a conservative but dogmatically minimalistic understanding of the Christian religion that combined an intensely Christocentric, biblicist, and experiential piety with an activist-missionary and eschatological orientation - a package which was now equated with being truly "Protestant" or "protestantisch," respectively. This reflects how the historical development of "Protestantism" intersected with larger philosophical and theological debates about "religion" and the different "religions" of humanity that involved Enlightenment thinkers as much as awakened Christians. The distinct version of "the Protestant religion" that first developed among the correspondents of this network would continue to evolve through the transatlantic awakenings of the eighteenth century and remain influential into the nineteenth century.
Online veröffentlicht von Cambridge University Press: 26. März 2021
Gesehen am 16.10.2024